Fundamentals of Sustainable Urban Renewal in Small and Mid-Sized Towns - Friedman, Avi (Springer International Publishing, 2018)
The book introduces challenges affecting smaller urban communities with fewer than 50,000 inhabitants and offers urban planning and building/architectural strategies to strengthen their city centers. It divides urban renewal of small towns into sub-components such as environmental challenges, demographic trends, economic changes and cultural aspects, and aging infrastructure. In each, context is established, and principles are outlined and illustrated. Topics include urban form, mobility and connectivity, infill neighborhoods design, wealth generation, and promotion of local culture and well‐being. Reinforced with detailed case studies, Fundamentals of Sustainable Urban Renewal in Small and Mid‐Sized Towns is an ideal resource for municipal planners, architects, civil engineers, and policy makers. Raises important questions on planning, urban design, and sustainability not previously covered by books devoted solely to large metropolitan regions; Presents a unique, systematic approach to the architecture, planning, and retooling of small towns that emphasizes the capacity for urban design to promote social regeneration and vitality; Suggests innovative strategies that tie theory and practice and offer a comprehensive primer to contemporary planning issues; Discusses a range of long-term strategies, anchored in principles of sustainable development, describing how to place a town on sustainable footing.